PENGARUH PEMBERIAN EKSTRAK ETANOL BIJI PEPAYA (Carica papaya L.) TERHADAP KETEBALAN LAPISAN OTOT POLOS TUBA FALLOPII TIKUS PUTIH BETINA GALUR WISTAR - Ega Prosfera, Rahma Haryunita; Eviana Norahmawati; Miftahul Jannah (Universitas Batam, 2024)
Many hormonal contraceptives users are many have experienced to drop out due to the side effects, which so it made the background to use natural materials, namely plants as alternative contraception because their side effects are relatively small. Papaya seeds are one part of the plant that contains antifertility ingredients such as alkaloid, saponin, and tannin compounds which are thought to interfere with hormonal processes in the body. This study aim to determine the effect of papaya seed ethanol extract on the thickness of the fallopian tube smooth muscle layer in female white rats. This study was a true experimental design with a randomized post test only control design conducted in November 2019-January 2020 were divided into 4 treatment groups namely 1 control group (without treatment) and 3 treatment groups (dose P1 0,1 mg/g BB, P2 0,2 mg/g BB, and P3 0,3 mg/g BB).The checking method in this study by measuring the thickness of the fallopian tube smooth muscle layer on histopathology anatomy slides of fallopian tube through HE staining. The measurements using a Dot Slide Olympus BX51 Microscope with an Olyvia application. Data analysis use Saphiro Wilk test, Levene test, One Way ANOVA test, and Post Hoc test with Tukey HSD using SPSS 25. The results of this study were effect of papaya seed ethanol extract take effect to reduce the thickness of the fallopian tube smooth muscle layer in the treatment group as the dose given papaya seed ethanol extract with the optimal dose is 0,3 mg/g BW.